Stičišča v "maturitetnih" romanih Otroške stvari in Otroštvo - Zupan Sosič, Alojzija (Jezik in slovstvo, 2015)
The novels for the matriculation examination, Otroške stvari (2003, Things of Childhood) by Lojze Kovačič (1928-2004) and Otroštvo (1983, Childhood) by Nathalie Sarraute (1902-1999) have many parallels, which are divided into story and narrative parallels in the present article. Story parallels are connected by collective topics and the similarity of the main character: a child. The two novels share (common) themes such as childhood, love, friendship, individuality, creativeness, empathy, art, homeland, language and education. The common features of Bubi and Nataša are individuality, a strong personality, a rich imagination and a talent for art, as well as suffering due to conflicts between their parents. Apart from the story parallels, there are also narrative parallels: the poetics of modernism, a fragmentary style, description and dialogue as a means of making narrative closer to the present, an "essay style", the point of view of a child, and the unreliable narrator. Both novels are modernistic autobiographical novels and Bildungsromans, in which the protagonists' memories are stimulated by the poetics of the fragment; Kovačič's memory acts as an accumulation of descriptions, while Sarraute activates memory through so-called "tropismes" (reminiscent words).
Keywords: Kovačič, Lojze, 1928-2004; "Otroške stvari"; Sarraute, Nathalie, 1901-1999; "Otroštvo"; Slovene literature; slovenska književnost; francoska književnost; French literature; podobnosti; fragmentarnost; pripovedni opis; nezanesljivi pripovedovalec; otroška perspektiva; matura